2016
DOI: 10.1007/s12291-016-0610-9
|View full text |Cite
|
Sign up to set email alerts
|

Lead as a Risk Factor for Osteoporosis in Post-menopausal Women

Abstract: Lead exposure is increasingly becoming an important risk factor for osteoporosis. In adults, approximately 80-90 % of absorbed lead is stored in the bones. These bone lead deposits are released into the blood during periods of enhanced bone resorption like menopause, forming a potential endogenous source of lead exposure. Postmenopausal women are at a higher risk for bone lead release because of hormonal and age related changes in bone metabolism. Estrogen deficiency is associated with increase in osteoclasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
6
0
2
Order By: Relevance
“…A comparison of studies between those reporting relevant effects versus no relevance for MetS on BMD indicates that the studies involved different races or nationalities (4, 17, 32). For example, some works involved menopausal Turkish women (17, 23), and post-menopausal Tibetan women (4). Some studies have reported differences in bone health and bone density-related disease among races and countries (34), which have been confirmed by studies presenting the prevalence of osteoporosis in menopausal women in each country (35–36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of studies between those reporting relevant effects versus no relevance for MetS on BMD indicates that the studies involved different races or nationalities (4, 17, 32). For example, some works involved menopausal Turkish women (17, 23), and post-menopausal Tibetan women (4). Some studies have reported differences in bone health and bone density-related disease among races and countries (34), which have been confirmed by studies presenting the prevalence of osteoporosis in menopausal women in each country (35–36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, research has shown inconsistent results regarding the relationship between MetS and BMD in menopausal women, and the correlation and causation are still unclear. Nevertheless, considering a report of low BMD in Asian women compared to Caucasians (22) and recent studies (10, 23) that continue to highlight the health problems of menopausal women, especially a decrease in BMD by MetS, it is necessary to make continuous attempts to elucidate the relationship between the two variables. Moreover, while Korea has focused on treatment for menopausal women with osteoporosis, its efforts at prevention by identifying and reducing potential risk factors have been relatively limited (2425).…”
Section: Introductionmentioning
confidence: 99%
“…Because, Pb and its compounds interfere with the functions of different organs and systems such as, the nervous system, the hematopoietic system, liver, and kidney 9 . Pb intoxication may cause blood vessels and tissue inflammation, making more calcium to be dragged to the area as a buffer and resulting in stiffening of the arterial walls with progressive blockage of the arteries and osteoporosis 14 , 15 . Since calcium is a critical ion in neuronal function, including cell growth and differentiation, neurotransmitter release, and intracellular biochemical cascades 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Denkbar wäre die Situation einer erhöhten beruflichen Belastung mit den Knochenstoffwechsel beeinflussenden Substanzen, z. B. Blei oder Kadmium, und einer daraus resultierenden, in der Knochendichtemessung nachgewiesenen Osteoporose[7,8]. Die geschilderte Osteoporose wäre dann in Zusammenhang mit einer Berufskrankheit zu beurteilen.…”
unclassified